2013
DOI: 10.1371/journal.pone.0071515
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Investigation into Strain Heterogeneity and Pathogenic Potential of the Emerging Gastrointestinal Pathogen Campylobacter ureolyticus

Abstract: The recent detection and isolation of C. ureolyticus from patients with diarrhoeal illness and inflammatory bowel diseases warrants further investigation into its role as an emerging pathogen of the human gastrointestinal tract. Regarding the pathogenic mechanisms employed by this species we provide the first whole genome analysis of two C. ureolyticus isolates including the type strain. Comparative analysis, subtractive hybridisation and gene ontology searches against other Campylobacter species identifies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 124 publications
(181 reference statements)
2
36
0
Order By: Relevance
“…This implication was confirmed by their further studies on C. ureolyticus pathogenicity and growth control imposed on the species present in the intestine (O'Donovan et al, 2014). Other studies indicated that this emerging pathogen can cause a gastrointestinal illness via destruction of cell structures (Garmory and Titball, 2004), relocating across the cell using various proteins such as zona occludens toxin (Zot) and secreted fibronectin-binding proteins (CadF and FlpA) (Bullman et al, 2013), or forming biofilms (Burgos-Portugal et al, 2012). Because the studies regarding the role of Campylobacter in gastroenteritis are still in their infancy, more research is needed to fully understand the relation between Campylobacter species and gastrointestinal diseases.…”
Section: Gastroenteritismentioning
confidence: 81%
“…This implication was confirmed by their further studies on C. ureolyticus pathogenicity and growth control imposed on the species present in the intestine (O'Donovan et al, 2014). Other studies indicated that this emerging pathogen can cause a gastrointestinal illness via destruction of cell structures (Garmory and Titball, 2004), relocating across the cell using various proteins such as zona occludens toxin (Zot) and secreted fibronectin-binding proteins (CadF and FlpA) (Bullman et al, 2013), or forming biofilms (Burgos-Portugal et al, 2012). Because the studies regarding the role of Campylobacter in gastroenteritis are still in their infancy, more research is needed to fully understand the relation between Campylobacter species and gastrointestinal diseases.…”
Section: Gastroenteritismentioning
confidence: 81%
“…Bullman et al 14 conducted whole genome analysis of at least 12 C. ureolyticus strains (CIT01–CIT13) which were isolated from animal reservoirs, asymptomatic patients, and patients with diarrheal illness, the initial results of which suggest substantial heterogeneity between different C. ureolyticus strains, supported by comparisons of whole genome coding sequences between these strains. It was demonstrated that 2–20% of their proteins are unique based on paired genome comparison of the coding sequences of 14 C. ureolyticus strains.…”
Section: Strain Heterogeneitymentioning
confidence: 99%
“…There have been 2 genes identified, unique to DSMZ 20703, that code for the production of the HecA protein, a member of the filamentous hemagglutinin adhesin (FHA) family. The hecB locus has been identified directly upstream of the hecA genes and codes for a hemolysin activation protein 14 . The protein products of these genes form a two-partner secretion (TPS) system, in which a TpsA family exoprotein (with a specific conserved secretion signal) is recognized by the associated TpsB family channel-forming transporter permitting passage through the membrane 75 .…”
Section: Secretome and Virulence Factors/toxinsmentioning
confidence: 99%
“…In 2012, Burgos-Portugal et al showed that C. ureolyticus has the ability to attach and translocate to human intestinal epithelial cells (8). Thereafter, analysis of the whole genome sequence of C. ureolyticus was carried out, and at least 106 potential virulence-related genes were found in this species (9). Therefore, C. ureolyticus has been considered to be potentially pathogenic.…”
Section: )mentioning
confidence: 99%